The CDC's Division of Adolescent and School Health Approach to Sexual Health Education in Schools: 3 Decades in Review. (29th December 2021) - Szucs, Leigh E.; Barrios, Lisa C.; Young, Emily; Robin, Leah; Hunt, Pete; Jayne, Paula E.
ABSTRACT: Background: School health education, including sexual health education, plays a crucial role in shaping adolescents' protective health behaviors, experiences, and outcomes. Adolescents need functional knowledge and skills to practice, adopt, and maintain healthy behaviors for preventing sexually transmitted infections (STIs), including human immunodeficiency virus (HIV), and unintended pregnancy. Methods: The US Centers for Disease Control and Prevention's Division of Adolescent and School Health (CDC/DASH) has advanced school‐based approaches to STI/HIV and pregnancy prevention through surveillance, research and evaluation, and program partnership and collaboration for over 3 decades. Results: CDC/DASH uses systematic and innovative strategies to identify the breadth of adolescent sexual health evidence; characterize key elements of effective educational curricula; and provide practical guidance to support school‐based delivery. CDC/DASH's approach to effective health and sexual health education in schools has changed dramatically over the past 30 years and must continue to progress. Conclusion: This paper describes how and why that approach has evolved and outlines directions for the future.